2021
DOI: 10.1371/journal.pone.0254620
|View full text |Cite
|
Sign up to set email alerts
|

Constructing robust and efficient experimental designs in groundwater modeling using a Galerkin method, proper orthogonal decomposition, and metaheuristic algorithms

Abstract: Estimating parameters accurately in groundwater models for aquifers is challenging because the models are non-explicit solutions of complex partial differential equations. Modern research methods, such as Monte Carlo methods and metaheuristic algorithms, for searching an efficient design to estimate model parameters require hundreds, if not thousands of model calls, making the computational cost prohibitive. One method to circumvent the problem and gain valuable insight on the behavior of groundwater is to fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…In addition, Masoudi et al (2019) applied ICA and found Bayesian optimal designs and, both Zhang et al (2020) and Liu et al (2021) modified the CSO algorithm and found optimal designs for different types of regression models with random effects. A most recent application using PSO and Genetic Algorithm is described in Ushijima et al (2021), where they found efficient designs for groundwater models after the complex models were simplified using a Galerkin method and a Proper Orthogonal Decomposition.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Masoudi et al (2019) applied ICA and found Bayesian optimal designs and, both Zhang et al (2020) and Liu et al (2021) modified the CSO algorithm and found optimal designs for different types of regression models with random effects. A most recent application using PSO and Genetic Algorithm is described in Ushijima et al (2021), where they found efficient designs for groundwater models after the complex models were simplified using a Galerkin method and a Proper Orthogonal Decomposition.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to numerous applications of metaheuristics in engineering and computer science, metaheuristics has also found applications ranging from addressing substantiability issues 85 to land use 19 and agriculture 58 . See also 86 , who used metaheuristic algorithms to design placements of the groundwater wells in the Los Angeles Basin.…”
Section: Estimation Problemsmentioning
confidence: 99%
“…Optimal experimental design (OED) is a method of designing experiments which uses an objective approach to elicit data containing "optimal information" for model calibration (Lindley et al, 1956;Kiefer, 1959;Smucker et al, 2018). It is extremely popular in physical sciences such as geosciences (Ushijima and Yeh, 2013;Seidler et al, 2016;Ushijima et al, 2021), mechanical engineering (Wickham et al, 1995;Gupta and Dhingra, 2013), chemical engineering (Rodriguez-Fernandez et al, 2007;Gottu Mukkula and Paulen, 2017;Schenkendorf et al, 2018), etc. In this study, we apply the techniques of OED to cardiac cellular electrophysiology to expedite the development of AP models suitable for both basic research and safety-critical applications.…”
Section: Introductionmentioning
confidence: 99%